Assessment Of the Ground and Construction Condition of the Arch "Ak-Saray" in Shakhrisabz - T.F.N., Dots. Shadmanova Z.S; Master Karaboev D. A (Genius Journals, 2022)
As a result of a comprehensive approach to the engineering problems of the arch "White Palace" in Shakhrisabz, their technical condition is determined, the physical and mechanical properties of the soil and the state of materials are studied.
Keywords: White House; engineering analysis; technical condition; research; monument; dome